Baseline characteristics and outcomes of patients with COVID-19 admitted to the intensive care unit in Armed Force Hospital, Oman: A single center cohort - Masoud Kashoub; Mohammed Al Shukairi; Mariya Al Abdali; Anisa Al Jabri; Rawan Al Abdulsalam; Jawahir Al Badri; Sachin Jose; Omar Al Salti (Clinical Epidemiology and Global Health)
Introduction: Amidst the global COVID-19 pandemic, characterized as the most catastrophic health crisis since the 1918 influenza pandemic, this study aims to provide local insights by examining critically ill patients with COVID-19 admitted to the Intensive Care Unit (ICU) at Armed Force Hospital (AFH) in Muscat, Oman. Methodology: This single-center retrospective cohort study encompassed 226 adult patients with laboratory-confirmed SARS-CoV-2 infection admitted between February 2020 and November 2021. Demographic information, clinical records, laboratory results, and radiological examinations were extracted from the AFH electronic system. Survival analysis employed the Kaplan-Meier curve to determine median survival time with a 95 % confidence interval. Univariate and multivariate Cox regression analyses were conducted to assess the impact of predictor variables on mortality, with hazard ratios reported alongside their 95 % confidence intervals. Results: The patient population exhibited a median age of 61 years, comprising 32.9 % females and 67.1 % males. A substantial majority, 84.7 % of patients, had at least one medical comorbidity. Notably, patients aged 65 years and older experienced an 83.3 % increased hazard of mortality, while each one-unit increase in lactate levels resulted in an 11.2 % increased hazard of mortality among ICU patients. The overall median survival time was found to be 17.00 days, with a 95 % confidence interval spanning from 14.18 to 19.82. Conclusion: The overall mortality rate observed in this study was approximately 56.5 %. These findings underscore the significant burden imposed by COVID-19 and highlight the imperative for the development of future strategies to mitigate similar outcomes in the face of future pandemics.